2017
DOI: 10.1016/j.jcrs.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

New parameters for evaluating corneal biomechanics and intraocular pressure after small-incision lenticule extraction by Scheimpflug-based dynamic tonometry

Abstract: The biomechanically corrected IOP measured after surgery with the dynamic Scheimpflug analyzer showed better agreement with the preoperative values than IOP. The stiffness parameter was not dependent on the amount of removed corneal thickness. A new sign correlated with dynamic corneal densitometry was found and might be related to changes in corneal hydration and biomechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…It was not surprising, since SSI re ected the corneal stiffness, and IOP measurement was affected by corneal stiffness 10,34 . While it was emphasized that bIOP can exclude the in uence of corneal thickness and age on intraocular pressure measurement 35 , and can re ect more accurate intraocular pressure [36][37][38] . Besides IOP, previous studies have shown that, parameters of corneal biomechanics in vivo were mostly affected by bIOP such as de ection area at the highest concavity and de ection amplitude (HC DefArea and HC DefA), SP -A1 38 CH and CRF 39 .…”
Section: Resultsmentioning
confidence: 99%
“…It was not surprising, since SSI re ected the corneal stiffness, and IOP measurement was affected by corneal stiffness 10,34 . While it was emphasized that bIOP can exclude the in uence of corneal thickness and age on intraocular pressure measurement 35 , and can re ect more accurate intraocular pressure [36][37][38] . Besides IOP, previous studies have shown that, parameters of corneal biomechanics in vivo were mostly affected by bIOP such as de ection area at the highest concavity and de ection amplitude (HC DefArea and HC DefA), SP -A1 38 CH and CRF 39 .…”
Section: Resultsmentioning
confidence: 99%
“…However, only A1 deflection length was significantly between control eyes and eyes having laser in situ keratomileusis (LASIK), femtosecond lenticule extraction or small‐incision lenticule extraction in another study . There is ongoing debate about the changes in corneal biomechanical properties with LASIK compared to small‐incision lenticule extraction (SMILE) . The A1 stiffness parameter changes independently of the lenticule thickness in SMILE surgery and corneal refractive surgery, in contrast to other dynamic corneal response factors, which correlated highly with lenticule thickness …”
Section: Discussionmentioning
confidence: 96%
“…There is ongoing debate about the changes in corneal biomechanical properties with LASIK compared to small‐incision lenticule extraction (SMILE) . The A1 stiffness parameter changes independently of the lenticule thickness in SMILE surgery and corneal refractive surgery, in contrast to other dynamic corneal response factors, which correlated highly with lenticule thickness …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations